2015
DOI: 10.3892/ol.2015.3968
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal inclusion cyst of the breast: A literature review

Abstract: Abstract. An epidermal inclusion cyst (EIC) of the breast is a rare, benign condition that may potentially be malignant. The present study conducted a systematic review of the literature in order to identify pathological hypotheses, clinical characteristics, and diagnostic and treatment options. A search for relevant studies was conducted through the Scopus, Embase and Medline databases during September 2014. The search term employed was ῾epidermal inclusion cyst breast᾽. Studies were selected if they containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 27 publications
0
69
0
Order By: Relevance
“…International literature has reported 90 cases of EIC of the breast. 22 Two patients in our study (2.46%) showed benign phyllodes; one was in forth decade and other was in fifth decade. These findings were compatible with Forae GD and Olu-Eddo et al 23 where benign phyllodes tumour constituted 1.8% of BBDs and most commonly encountered between the third and fifth decades of life.…”
Section: Discussionmentioning
confidence: 56%
“…International literature has reported 90 cases of EIC of the breast. 22 Two patients in our study (2.46%) showed benign phyllodes; one was in forth decade and other was in fifth decade. These findings were compatible with Forae GD and Olu-Eddo et al 23 where benign phyllodes tumour constituted 1.8% of BBDs and most commonly encountered between the third and fifth decades of life.…”
Section: Discussionmentioning
confidence: 56%
“…Presentation of an epidermal cyst as a breast lump in a male patient is an unusual condition [4]. To the best of our knowledge, only 8 male patients with epidermal cysts of the breast have been reported in the English literature [5]. Epidermal cyst of the breast in a male patient should be differentiated from benign and malignant lesions such as gynecomastia, lipoma, intraductal papilloma, subareolar abscess, hematoma, fibroadenoma, invasive ductal carcinoma, papillary carcinoma and primary lymphoma of the breast.…”
Section: Dear Editormentioning
confidence: 99%
“…Cameron and Hilsinger [6] reported that malignant transformation of the cyst wall epithelium occurs very rarely (0.045%). Asymptomatic small sized lesions (<2cm diameter), if diagnosis is certain, do not require treatment [7]. Symptomatic, palpable lesions causing the patient physical and psychological discomfort, should be readily excised and need histological correlation to rule out any potential complications that can arise from these cysts [8].…”
Section: Commentsmentioning
confidence: 99%